The prophylactic antiemetic therapies in management of differentiated thyroid cancer patients with radioactive iodine therapy: a single-center, non-randomized clinical trial - Li, Xiao; Cao, Jingjia; Wang, Wenxiu; Zhu, Xiaolu; Sun, Yaru; Song, Lei; Zhang, Wei; Han, Yong (Frontiers in Endocrinology, 2024)
Objective: The present study was to investigate three different single-drug regimens to show which was more effective to reduce radioactive iodine therapy (RAI) associated nausea and vomiting, and to compare the occurrence of long-term gastrointestinal diseases after RAI therapy.We performed a single-center, non-randomized clinical trial among patients who underwent RAI therapy from March 2016 to July 2022. Enrolled patients were divided into four cohorts based on the date of the treatment. cohort 1, with no preventive antiemetics; cohort 2, received 20 mg of pantoprazole per day for 3 days; cohort 3, received a 10 mg metoclopramide tablet two times daily for 3 days; cohort 4, oral ondansetron, 8 mg, twice daily for 3 days. The primary endpoints were proportion of patients who experience vomiting episodes and nausea during the 7-day hospital period. Secondary end points included Functional Living Index Emesis (FLIE) quality-of life questionnaires and the occurrence of gastrointestinal diseases.Results: A total of 1755 patients were analyzed, comprised of 1299 (74.0%) women and 456 (26.0%) men, with a median age of 44 years (range 18-78 years). The characteristics of patient were similar within the four groups. 465 (26.4%) patients developed RAI-associated nausea, and 186 (14.4%) patients developed RAI-associated vomiting. The rate of nausea was significantly decreased in the patients who were taking ondansetron when compared with the other cohorts (P<0.05), while the rate of vomiting (≥6 episodes) was slightly lower. As secondary endpoint, FLIE measures ondansetron scored highly compared to other cohorts, from baseline (mean score of 110.53±17.54) to day 7 (mean score of 105.56 ±12.48). In addition, 48 (2.7%) patients were found to be with gastrointestinal diseases at the end of one year follow up. Multiple RAI therapy and higher dose of I-131 per body weight revealed a significantly independent risk factors of developing gastrointestinal disorders.In conclusion, the present study demonstrated that short-term ondansetron could be an effective prophylactic agent in controlling RAI-associated nausea and vomiting. Furthermore, the risk of developing gastrointestinal disorders was significantly higher for patients with multiple RAI therapy and higher dose of I-131 per body weight.